A new species of Leptolalax (Anura: Megophryidae) from northeastern Cambodia - Rowley, Jodi J. L.; Stuart, Bryan L.; Thy, Neang; Emmett, David A. (Zootaxa, 2010)
We describe a new species of megophryid frog in the genus Leptolalax from the Kon Tum Plateau in northeastern Cambodia. Leptolalax melicus sp. nov. is distinguished from its congeners by a combination of an off-white to pale pink ventral surface with diffuse dark brown blotches and distinct white speckling, finger I < II, an absence of webbing and dermal fringes on fingers, slight basal webbing and no dermal fringes on toes, body size (19.5–22.7 mm for seven adult males), an absence of ventrolateral glandular lines, dorsum mostly smooth with no skin ridges, and a unique advertisement call consisting of a single long introductory note containing 8–50 pulses, followed by 3–11 predominantly single-pulsed notes, and with an average dominant frequency of 3560–3610 Hz. Leptolalax melicus can be further distinguished from the morphologically similar L. applebyi in having more distinct dorsal patterning, and significantly larger pectoral and femoral glands. Leptolalax melicus and L. applebyi also differ by 6.1% sequence divergence at the 16S mtDNA gene. All specimens of L. melicus were found near rocky streams in evergreen forest between 650–850 m elevation. We suggest the new species should be considered Data Deficient following IUCN’s Red List categories.